Novel bifunctional peptidic aspartic protease inhibitor inhibits chitinase A from Serratia marcescens: kinetic analysis of inhibition and binding affinity - Kumar, Ajit; Rao, Mala (Biochimica Et Biophysica Acta-General Subjects, 2010)
Background: Chitinase inhibitors have chemotherapeutic potential as fungicides, pesticides and antiasthmatics. The majority of chitinase inhibitors reported are natural products like argifin, argifin linear fragments, argadin, allosamidin and disulfide-cyclized peptides. Here, we report a novel peptidic inhibitor API (Aspartic Protease Inhibitor), isolated from Bacillus licheniforrnis that inhibits chitinase A (ChiA) from Serratia marcescens. Methods: The binding affinity of API with ChiA and type of inhibition was determined by the inhibition kinetics assays. Fluorescence and CD spectroscopic analysis and chemical modification of API with different affinity reagents elucidated the mechanism of binding of API with ChiA. Results and conclusions: The peptide has an amino acid sequence N-Ile(1)-Cys(2)-Glu(3)-Ala(4)-Glu(5)-His(6)-Lys(7)-Trp(8)-Gly(9)-Asp(10) -Tyr(11)-Leu(12)-Asp(13)-C. The ChiA-API kinetic interactions reveal noncompetitive, irreversible and tight binding nature of API with I-50= 600 nM and K-i = 510 nM in the presence of chromogenic substrate pnitrophenyl-N,N'-diacetyl-beta-chitobioside[p-NP-(GIcNAc)(2)]. The inhibition progress curves show a two-step slow tight binding inhibition mechanism with the rate constant k(5) = 8.7 +/- 1 x 10(-3) s(-1) and k(6) = 7.3 +/- 0.6 x 10(-5) s(-1). CD-spectra and tryptophanyl fluorescence analysis of ChiA incubated with increasing API concentrations confirms conformational changes in enzyme structure which may be due to irreversible denaturation of enzyme upon binding of API. Chemical modifications by WRK abolished the anti-chitinase activity of API and revealed the involvement of carboxyl groups in the enzyme inactivation. Abolished isoindole fluorescence of OPTA-labeled ChiA demonstrates the irreversible denaturation of ChiA upon incubation with API for prolonged time and distortion of active site of the enzyme. General significance: The data provide useful information that could lead to the generation of drug-like, natural product-based chitinase inhibitors. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Aspartic protease inhibitor; Bacillus licheniformis; Chitinase A; Enzyme kinetics; Slow tight binding inhibition